Delayed activation of PPAR-β/δ improves long-term survival in mouse sepsis: effects on organ inflammation and coagulation. Issue 4 (May 2018) - Busch, Daniel; Kapoor, Amar; Rademann, Pia; Hildebrand, Frank; Bahrami, Soheyl; Thiemermann, Christoph; Osuchowski, Marcin F
Activation of peroxisome proliferator-activated receptor (PPAR)-β/δ reduces tissue injury in murine endotoxemia. We hypothesized that the PPAR-β/δ-agonist GW0742 improves long-term outcome after sepsis caused by cecal ligation and puncture (CLP). Fifty-one CD-1 female mice underwent CLP and received either vehicle (control), GW0742 (0.03 mg/kg/injection; five post-CLP i.v. injections), GSK0660 (PPAR-β/δ-antagonist) or both and were monitored for 28 d. Another 20 CLP mice treated with GW0742 and vehicle were sacrificed 24 h post-CLP to assess coagulopathy. Compared to vehicle, survival of CLP-mice treated with GW0742 was higher by 35% at d 7 and by 50% at d 28. CLP mice treated with GW0742 had 60% higher IFN-γ but circulating monocyte chemoattractant protein-1 and chemokine ligand were lower at 48 h post-CLP. Compared to vehicle, CLP mice treated with GW0742 exhibited a 50% reduction in the circulating plasminogen activator inhibitor-1 associated with an increase in platelet number at 24 h post-CLP (but no changes occurred in anti-thrombin-III, plasminogen, fibrinogen and clotting-times). CLP mice treated with GW0742 exhibited a similar increase in most of the biochemical markers of organ injury/dysfunction (lactate dehydrogenase, alanine aminotransferase, creatine kinase, creatinine, blood urea nitrogen, and triglycerides) measured. Treatment with GW0742 consistently improved long-term survival in septic CD-1 mice by partially modulating the post-CLP systemic cytokine response and coagulation systems.